SYSTEMATIC LAYOUT PLANNING FOR CONTAINER TERMINAL SYSTEM WITH FLOW ANALYSIS - Andre Sugiyono (International Conference on Industrial Revolution for Polytechnic Education, 2021)
Although many new approaches have been developed in facility planning, the Systematic Layout Planning (SLP) procedure still appears to be widely used particularly for container terminal layout design. This paper presents a revised Systematic Layout Planning which can address some of the limitations on its application for Container Terminal System (CTS). According to the literature SLP lacks a method to use information on containers handling routings as input data, and it does not have the ability to generate layouts that are a hybrid combination of functional and cellular layouts for CTS. SLP is based on aggregation of an Activity Relationship Chart and/or a From-To-Chart into an Activity Relationship Diagram. This is followed by the determination of the amount of space required to be assigned to each activity and the availability of that space for CTS. However, Flow Analysis can be incorporated to the method to identify causes of delay in containers flows such as complex operation sequences at CTS, high volume, variety of equipments, ineffective facility layout, and inappropriate assignment of equipments for operations. This study suggest that the integration of flow analysis in the enhanced SLP for CTS can be done to achieve a better layout design methodology. Moreover, using SLP with flow analysis approach can provide a higher flexibility to cope with fluctuations are common in the process.